Histomorphometric Study Regarding the Effect of Experimental Exposure of Carassius gibelio Species to Increasing Doses of Ethylenediaminetetraacetic Acid(EDTA) - Marioara Nicula; Gabi Dumitrescu; Eliza Simiz; Liliana Petculescu-Ciochină; Nicolae Păcală; Adela Marcu; Valeriu Carabă; Simina Neo (Scientific Papers Animal Science and Biotechnologies, 2023)
The aim of this paper is to show the preliminary results regarding some histomorphometrical changes induced by chronic exposure of Prussian carp specimens to increasing doses of EDTA.